1977
DOI: 10.1161/01.cir.55.2.279
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of postmortem anatomic findings with electrocardiographic changes in patients with myocardial infarction: retrospective study of patients with typical anterior and posterior infarcts.

Abstract: SUMMARY This retrospective study correlates electrocardiographic and histopathologic findings in 24 patients with single wellcircumscribed infarcts to determine 1) whether ECG terms commonly used to describe the location of myocardial infarcts are significant, and 2) whether the extent of infarct can be determined using QRS characteristics. Transverse sections of the hearts were photographed. Based on histologic sections, the infarct was outlined on the photograph and each section was planimetered via a sonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
3

Year Published

1982
1982
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(64 citation statements)
references
References 31 publications
(8 reference statements)
2
59
0
3
Order By: Relevance
“…The area where ST-segment elevations were demonstrated on a l2-lead ECG always included the leads with newly developed , abnormal Q waves . The ECG findings during angina probably indicate that some viable myocardium remains in the area of MI as presented previously to clinicohistological studies (Savage et al ., 1977;Wilkinson et al, 1963) . During spontaneous angina in these patients, some viable myocardium within and surrounding the infarcted area might have become severely ischemic by myocardial oxygen supplydemand imbalance.…”
Section: Discussionsupporting
confidence: 70%
“…The area where ST-segment elevations were demonstrated on a l2-lead ECG always included the leads with newly developed , abnormal Q waves . The ECG findings during angina probably indicate that some viable myocardium remains in the area of MI as presented previously to clinicohistological studies (Savage et al ., 1977;Wilkinson et al, 1963) . During spontaneous angina in these patients, some viable myocardium within and surrounding the infarcted area might have become severely ischemic by myocardial oxygen supplydemand imbalance.…”
Section: Discussionsupporting
confidence: 70%
“…The 12-lead ECG has also been shown to be useful in estimating MI size (9). For this purpose the so called Selvester QRS scoring system was developed and validated by histopathology for different MI locations (10)(11)(12)(13) and by DE-MRI for chronic anterior MI (14).…”
Section: Introductionmentioning
confidence: 99%
“…According to ECG findings, patients are usually classified as transmural or subendocardial MI depending on the presence or absence of Q waves. This classification has been criticized in recent years since autopsy studies have shown that the presence of Q waves on standard ECG is not equivalent to transmural MI and transmural MI can occur without the development of Q waves (Savage et al, 1977;Sullivan et al, 1978). It has therefore been proposed that this type of subdivision should not be made on the basis of ECG findings (Pipberger and Lopez, 1980).…”
Section: Discussionmentioning
confidence: 99%